Comparison of fracture toughness values of normal and high strength concrete determined by three point bend and modified disk-shaped compact tension specimens - Stanislav Seitl; José D. Ríos; Hector Cifuentes (Fracture and Structural Integrity)
The modified disk shaped compact tension test is a configuration derived from standard compact tension test that is used for measuring fracture mechanical properties of primarily metallic materials. The compact tension configuration is commonly used for measurement fracture mechanical properties as e.g. fracture toughness, Young’s modulus, work of fracture etc. The modified compact tension tests imply significant modifications of the specimen morphology in order to avoid premature failure. The modified compact tension test is not proper for quasi-brittle materials due to its complicated shape (steel-concrete interface), but it is easily extracted from drill core and we do not need large amount of material for obtaining fracture properties as we need for e.g. three- or four- point bend test. Since it is a new test method, a wide range of tests is needed to be done before it can be applied. In the paper the selected outputs of the experiments performed on normal and high strength concrete will be processed and the values of fracture mechanical parameters will be discussed.